Human Embryonic Stem Cells as a Predictive Model for Developmental Toxicity and Disease: Reducing the Use of Animal Testing in Regulatory Toxicology - Eng, Tyler (Université d'Ottawa / University of Ottawa, 2023)
The recent expansion in chemical and manufacturing and innovation has led to a large influx of chemicals to the market, and subsequent release into the environment. Many of these new chemicals, as well as legacy chemicals are untested for their potential developmental toxicity, especially in early embryonic stages. This creates a need for a timely and cost-effective method for screening these chemicals. Furthermore, advances in in vitro methods and human pluripotent cell culturing techniques have revealed some weaknesses in our current animal model-based paradigms. Here we tested an in vitro model for developmental toxicity screening using human embryonic stem cells (hESCs) for environmental chemicals. In this study, hESCs were exposed to three known developmental toxicants that are prevalent in the environment, bisphenol A (BPA), perfluorooctane sulfonate (PFOS), or lead chloride (PbCl₂), at environmentally relevant concentrations of 0-2500 µg/L, 0-2275 µg/L, and 0-6200 µg/L respectively, for 6-days. hESCs were evaluated for dose responses on proliferation level by assaying cell viability, mitochondrial dehydrogenase activity (MDHA), cell confluency, and cell cycle distribution. Differentiation capability was assayed by induction of differentiation into ectoderm, mesoderm, and endoderm; hESCs and differentiated cells were then sequenced for their full transcriptome. Gene expression effects were analyzed by a single cell transcriptome sequencing and analysis of global DNA methylation. Proliferation and methylation effects were tested for all 3 chemicals, while differentiation and single cell sequencing was only tested on PbCl₂. Our results show hESCs were able to identify known and novel proliferation effects of BPA, PFOS, and PbCl₂, reflect differentiation level effects of PbCl₂, and elucidate molecular level drivers of these toxic effects. We also showed that hESCs responded to developmental toxicants at lower doses than in vivo models. In conclusion, our hESC-based model could act as an effective developmental toxicity screening tool for pre- peri- and post-implantation stages of embryo development.
Keywords: Human Embryonic Stem Cells; Toxicology; BPA; PFOS; Lead (Pb); Developmental Toxicity